TINJAUAN HUKUM TENTANG PENGADAAN BARANG DAN JASA OLEH PEMERINTAH (JURNAL HUKUM DAS SOLLEN, 2022)
Procurement of goods/services is essentially an effort by the user to obtain or realize the goods/services they need, by using certain methods and processes in order to reach an agreement on specifications, prices, times, and other agreements. In order for the purpose of the procurement of goods/services to be carried out as well as possible, both parties, namely the User and the Provider, must always adhere to the philosophy of the procurement of goods/services, comply with the ethics and norms of the procurement of goods/services that apply, follow the principles, standard methods and processes for the procurement of goods and services. Based on the description above, it is very necessary to do a basic research on how the procedures / stages of the implementation of the Procurement of Goods and Services by the Government, and how legal remedies can be taken by the parties in the event of a violation of the law in the implementation of the procurement of goods and services aimed at all parties involved in the procurement of goods and services. involved in the procurement of goods and services can understand the stages of the procurement of goods and services and legal remedies in case of deviations, to achieve these goals using the normative juridical method, so that it can be concluded that the regulation on the procurement of goods and services is quite good, but in practice there are deviations by unscrupulous government officials, and any dispute decided by the court related to the procurement of goods and services should be carried out by the relevant parties.